A ESTIMATING MALAYSIAN ECOTOURISM DEMAND USING FUZZY MODEL (CASE STUDY OF STATE OF MALACCA) - YOUSEF ROSTAMI (ASEAN Journal on Hospitality and Tourism, 2007)
Fuzzy regression model (FRM) is an alternative to evaluate the relation between variables among the forecasting models, when the data are not sufficient to identify the relation and we have uncertainty in data. Behavior and thinking of the people, with their differences on emotions and intuitions, produce the ambiguity in social studies. Instead of using point estimation in conventional probability theory, fuzzy set theory can be used to granulate a concept into a set with membership function and thus decreases the amount of required data. In the last two decades, Fuzzy Sets Theory that was introduced in 1965 by Prof. Lotfi A. Zadeh has received wide attention particularly with successful applications in various fields ranging from engineering to social science studies. Besides being an alternative to Conventional Regression Model (CRM), the Fuzzy Regression Model (FRM) has the ability to evaluate relationships between variables when the data series are limited and uncertain. Moreover, the fuzzy regression is able to address the ambiguity in the variables, such as human behavior, thinking and subjectivity. In this paper, we estimate the demand model for ecotourism in Malacca state by using FRM as an alternative approach. Results show that trip cost, opportunity cost, time and income are the significant variables that could explain variation in number of trip as dependent variable.